“Colombia, the only risk is wanting to stay” - Marie-Laure Guilland (Via@)
The link between risk or danger and Colombia is well established in the transnational imaginary and it is difficult to separate the two in the current ideological climate of international security. This imaginary of risk is so persistent that state-organised promotion of tourism is forced to take it into account in order to refute it. Foreign embassies, however, continue to present Colombia as a risky destination. At the same time, certain tourists, seeking meaning and intensity from their travel experience, use this imaginary of risk and play with stereotypes about Colombia during a trek in the Sierra Nevada de Santa Marta. Is the risk real or not ? It does not matter, as long as the imaginary of risk is shared. This process enables the ‘intrepid’ travellers to distinguish themselves from other tourists. In this way, the visitors insist on the imaginary of risk even as the Colombian authorities seek to minimise it.